The Effect of Replacement of a Partial Commercial Ran With Fermented Coconut Saves on Organ in Chicken Broiler (Gallus domesticus) - Heru Afrian; Supriyono Supriyono; Eko Joko Guntoro (Baselang, 2021)
This study aims to determine the effect of giving fermented coconut dregs to the internal organs of broiler chickens. This research was conducted at Jln. Garuda Sapta Mulya Village, Rimbo Bujang Subdistrict, Tebo Regency for 40 days from 6 April - 8 May 2019.            The design used was a completely randomized design (CRD) with 5 treatments and 4 replications, where each unit contained 5 DOCs. Each ration treatment was A0 (100% commercial ration), A1 (5% fermented coconut dregs + 95% commercial ration), A2 (10% fermented coconut dregs + 90% commercial rations), A3 (15% fermented coconut dregs + 85% commercial rations) and A4 (20% fermented coconut dregs + 80% commercial rations). The parameters observed were percentage of liver weight, percentage of proventriculus weight, percentage of ventricular weight, and percentage of small intestine length. Using the DNMRT test if it had a significant effect on all observed parameters, the coconut dregs used in this study were up to 20 levels %.             The results showed that the average percentage of liver weight was A0 (1.75), A1 (1.66), A2 (1.94), A3 (1.95), A4 (1.74). Mean percentage by weight of the proventriculus A0 (0.29), A1 (0.29), A2 (0.32), A3 (0.31), A4 (0.33). Average percentage by weight ventriculus A0 (1.05), A1 (1.15), A2 (1.13), A3 (1.23), A4 (1.37). Average percentage of small intestine length A0 (10.12), A1 (9.76), A2 (10.37), A3 (11.21), A4 (10.54). The effect of giving fermented coconut dregs to internal organs had a significant effect on the percentage of liver weight (P˂0.05) and the percentage of ventricular weight (P˂0.05). The provision of fermented coconut dregs did not significantly affect the percentage of proventriculus weight (P˃0.05) and the percentage of small intestine length (P˃0.05).                The conclusion in this study is that the effect of fermented coconut dregs has a significant effect on the percentage of liver and ventricular weight but does not have a significant effect on proventriculus weight and small intestine length, fermented coconut dregs can still be used as a substitute for commercial rations up to 20%.